2022
DOI: 10.3390/jcm11236927
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous-Associated Brain Damage May Lead to Anxiety and Depression

Abstract: Background and purpose: Anxiety and depression are common in patients with Cerebral venous outflow disturbance (CVOD). Here, we aimed to explore possible mechanisms underlying this phenomenon. Methods: We enrolled patients diagnosed with imaging-confirmed CVOD, including internal jugular venous stenosis (IJVS) and cerebral venous sinus stenosis (CVSS) between 2017 and 2020. All of them had MRI/PWI scans. The Hamilton Anxiety Scale (HAMA) and 24-item Hamilton Depression Scale (HAMD) were used to evaluate the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“… 83 Previous studies have indicated that CCH is closely associated with depression in animal models and humans. 84 85 …”
Section: Effect Of Gut Microbiota-derived Scfas On Depressionmentioning
confidence: 99%
“… 83 Previous studies have indicated that CCH is closely associated with depression in animal models and humans. 84 85 …”
Section: Effect Of Gut Microbiota-derived Scfas On Depressionmentioning
confidence: 99%